Projekts Uzņēmuma SIA "Alberta" dibināšana - Alberta, Arta (Latvijas Universitāte, 2014)
Maģistra darbā „Projekts: Uzņēmuma sabiedrība ar ierobežotu atbildību „Alberta” dibināšana” ir izstrādāts biznesa plāns jauna specializēta mazumtirdzniecības uzņēmuma dibināšanai. Projekta „Uzņēmuma sabiedrība ar ierobežotu atbildību „Alberta” dibināšana” mērķis ir sporta deju produktu un pakalpojumu pieejamības veicināšana, atverot specializēto deju piederumu veikalu „Virpuļo dejā” Rīgā, Brīvības ielā 59. Projekta īstenošanas laiks ir 88 dienas no 2014.gada 1.janvāra līdz 2014.gada 2.maijam.

The theme of Master thesis is: “Project: Limited liability company „Alberta” establishment”, where is worked up business plan for new dedicated retail trade company establishment. The goal of graduation work „Project: Limited liability company „Alberta” establishment” is dance sport product and services accessibility promotion by opening specialized dance sport accessory shop „To Whirl in dance”, address: Riga, street Brivibas 59. Project implementation time is 88 days – from the 1st January year 2014 till the 2nd May year 2014. Shop opening planned at the first dates of May in 2014.
Project SIA "Alberta" establishing
Keywords: Finanses un kredīts